Comparative gene expression of Wigglesworthia inhabiting non-infected and Trypanosoma brucei gambiense-infected Glossina palpalis gambiensis flies - Hamidou Soumana, Illiassou; Tchicaya, Bernadette; Simo, Gustave; Geiger, Anne (Frontiers in Microbiology, 2014)
Tsetse flies (Glossina sp.) that transmit trypanosomes causing human (and animal) African trypanosomiasis (HAT and AAT, respectively) harbor symbiotic microorganisms, including the obligate primary symbiont Wigglesworthia glossinidia. A relationship between Wigglesworthia and tsetse fly infection by trypanosomes has been suggested, as removal of the symbiont results in a higher susceptibility to midgut infection in adult flies. To investigate this relationship and to decipher the role of W. glossinidia in the fly's susceptibility to trypanosome infection, we challenged flies with trypanosomes and subsequently analyzed and compared the transcriptomes of W. glossinidia from susceptible and refractory tsetse flies at three time points (3, 10, and 20 days). More than 200 W. glossinidia genes were found to be differentially expressed between susceptible and refractory flies. The high specificity of these differentially expressed genes makes it possible to distinguish Wigglesworthia inhabiting these two distinct groups of flies. Furthermore, gene expression patterns were observed to evolve during the infection time course, such that very few differentially expressed genes were found in common in Wigglesworthia from the 3-, 10- and 20-day post-feeding fly samples. The overall results clearly demonstrate that the taking up of trypanosomes by flies, regardless of whether flies proceed with the developmental program of Trypanosoma brucei gambiense, strongly alters gene expression in Wigglesworthia. These results therefore provide a novel framework for studies that aim to decrease or even abolish tsetse fly vector competence.